2023
DOI: 10.1093/hr/uhad191
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping in a sweet cherry germplasm collection (Prunus avium L.) reveals candidate genes for fruit quality traits

Armel S L Donkpegan,
Anthony Bernard,
Teresa Barreneche
et al.

Abstract: In sweet cherry (Prunus avium L.), a large variability exists for various traits related to fruit quality. There is a need to discover the genetic architecture of these traits in order to enhance the efficiency of breeding strategies for consumer and producer demands. With this objective, a germplasm collection consisting of 116 sweet cherry accessions was evaluated for 23 agronomically fruit quality traits over two to six years, and characterized using a genotyping-by-sequencing (GBS) approach. The SNP covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…However, our findings demonstrate that a single gene, PavSCPL, with a 5.2-kb insertion, has led to firmer fruit in the F 1 population derived from the cross 'Rainier' 9 'Summit'. The AFLP markers of PavSCPL associated with fruit firmness developed in this study, as well as several SNPs markers associated with fruit firmness-related traits identified by Holu sov a et al (2022) and Donkpegan et al (2023) will be used for MAS in breeding improvement of the fruit firmness trait.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…However, our findings demonstrate that a single gene, PavSCPL, with a 5.2-kb insertion, has led to firmer fruit in the F 1 population derived from the cross 'Rainier' 9 'Summit'. The AFLP markers of PavSCPL associated with fruit firmness developed in this study, as well as several SNPs markers associated with fruit firmness-related traits identified by Holu sov a et al (2022) and Donkpegan et al (2023) will be used for MAS in breeding improvement of the fruit firmness trait.…”
Section: Discussionmentioning
confidence: 88%
“…For example, using the 'Ambrun es' 9 'Sweetheart' F 1 population, qP-FF1.1, qP-FF1.2 and qP-FF6.1 were identified, while only qP-FF4.1 was identified in the 'Fercer' 9 'X' (an unknown parent) F 1 population (Cai et al, 2019;Campoy et al, 2015). Meanwhile, several significant SNPs associated with the fruit firmness trait have been identified and localized with QTLs qP-FF1.1, qP-FF1.2, qP-FF4.1 and qP-FF6.1 in GWASs with 116 or 235 sweet cherry accessions (Donkpegan et al, 2023;Holu sov a et al, 2022), especially qP-FF4.1 (approximately 1.8 Mbp, 12 928 603-14 860 789 bp). Despite the identification of numerous SNP markers for the sweet cherry fruit firmness trait, few have been successfully applied to breeding for fruit firmness .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations